Exploring efficacy of spiritual-based interventions (SBIs) in addressing depressive symptoms among cardiac patients in MENA region: a scoping review - Amin, Rizwana (Frontiers in Psychology, 2025)
BackgroundDepression is a widespread psychological issue among patients with cardiac diseases, which affects treatment adherence, recovery, and overall quality of life. Spiritual-based interventions (SBIs) have gained attention for their potential to alleviate depressive symptoms. However, there is a dearth of research investigating the efficacy of these interventions in the Middle East and North Africa (MENA) region.ObjectiveThis scoping review aims to synthesize available evidence on the efficacy of spiritual-based interventions in reducing depressive symptoms among cardiac patients in the MENA region.MethodsThe present research used a systematic approach to searching electronic databases such as SCOPUS, Web of Science, and ESBECOhost Arab research world in the English language from 2015 to 2025, based on the Arksey and O'Malley framework. Papers were identified based on spiritual-based Intervention addressing depressive symptoms among cardiac patients in the MENA region. Studies were analyzed using the Population-Concept-Context (PCC) framework, as outlined in the Preferred Reporting Items for Systematic Reviews and Meta-Analyses for Scoping Reviews (PRISMA-ScR).ResultsThe analysis pinpoints numerous Spiritual Interventions, such as prayer, mindfulness, and Faith-based counseling, as usual practices. The results showed that SBIs are related to a decrease in depression symptomology and enhancement of psychological wellbeing. Nevertheless, variability in the study models, small amounts of samples, and sparse long-term studies are also some of the current study's limitations.ConclusionThis research indicates that the efficacy of spiritual-based interventions can reduce depressive signs in cardiac patients in the MENA region. However, additional research is required to ascertain long-term efficacy and cross-cultural effectiveness.